2021
DOI: 10.1007/s10802-021-00814-z
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Regulation as a Mediator in the Relationship Between Cognitive Biases and Depressive Symptoms in Depressed, At-risk and Healthy Children and Adolescents

Abstract: Contemporary cognitive models of depression propose that cognitive biases for negative information at the level of attention (attention biases; AB) and interpretation (interpretation biases; IB) increase depression risk by promoting maladaptive emotion regulation (ER). So far, empirical support testing interactions between these variables is restricted to non-clinical and clinical adult samples. The aim of the current study was to extend these findings to a sample of children and adolescents. This cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 101 publications
1
5
1
Order By: Relevance
“…In contrast to negative affect intensity, our nonsignificant findings for negative affect instability are somewhat unexpected based on work in adults (Puccetti et al, 2020) and prior research demonstrating associations between interpretation biases and trait emotion regulation (e.g., Sfärlea et al, 2021). First, discrepancies with Puccetti and colleagues (2020) may reflect developmental differences in the mechanisms underlying markers of daily affect in adults compared to early adolescents.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…In contrast to negative affect intensity, our nonsignificant findings for negative affect instability are somewhat unexpected based on work in adults (Puccetti et al, 2020) and prior research demonstrating associations between interpretation biases and trait emotion regulation (e.g., Sfärlea et al, 2021). First, discrepancies with Puccetti and colleagues (2020) may reflect developmental differences in the mechanisms underlying markers of daily affect in adults compared to early adolescents.…”
Section: Discussioncontrasting
confidence: 90%
“…This possibility is supported by related work on emotion regulation. Negative interpretations of ambiguity have been linked to the use of maladaptive emotion regulation strategies (e.g., brooding; Everaert, Grahek, et al, 2017; Wilson et al, 2006), which has been shown to mediate associations between more negative interpretation biases and greater depressive symptoms (Blanco et al, 2021; Sfärlea et al, 2021). Automatic and inflexible interpretations may also facilitate further mood‐congruent cognitions, thereby impairing the efficacy of more adaptive strategies such as cognitive reappraisal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies of adolescent depression and social anxiety support the adverse effect of interpretation biases on emotional experiences. Adolescents with depression or anxiety select more negative interpretations and fewer positive ones, across several different tasks (Haller et al, 2016; Lau & Waters, 2017; Leigh & Clark, 2018; Mobach et al, 2019; Oliver et al, 2019; Sfärlea et al, 2021; Stuijfzand et al, 2018). Preliminary evidence suggests that these biases are not merely consequences of depression or anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Frequent use of CR can modify an individual’s interpretation bias, dampen rumination bias, and thus alleviate depression symptoms (attention bias→interpretation bias→CR→rumination→depressive symptoms) ( Everaert et al, 2017 ). CR frequency mediated the relationship between interpretation biases and depressive symptoms in individuals at high familial risk for depression and alleviated the negative impact of interpretation bias on depressive symptoms (interpretation bias→CR→depressive symptoms) ( Sfärlea et al, 2021 ). Depression-resilient individuals tend to use CR to assign a new emotional meaning to stressful events ( Knyazev et al, 2017 ), whereas adolescents with parents having a history of depression (depression-vulnerable individuals) who frequently use CR as an emotion regulation strategy will experience less depression and have higher positive emotions ( Kudinova et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%